A Descriptive Look at the Factors Influencing the Geopolitics of Afghanistan: The Geopolitics of Afghanistan - Amiri, Ziaulhaq; Habibyar, Sharifullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
Geopolitics means the effect of the geographical location of the region on the policies of other governments. Afghanistan, as a landlocked country, is a strategic geographical area because of ​​its neighbors, and in principle, a country with a strategic position is inevitably part of the military strategy. Afghanistan also has this potential, so Afghanistan's geopolitical attractions have attracted the attention of superpowers from the past to the present. Understanding geopolitical codes is one of the factors that politicians of any government should try to identify to use the appropriate strategy to establish a strong diplomatic relationship with other countries.